Online microfinance in Eastern Europe: Personal versus business loans funding - Matias Gama, Ana Paula (2020)
Across the European Union, the market size of crowdfunding totals €16.9 billion with 1,231 active platforms (Chervyakov and Rocholl, 2019). However, the shares of microcredit (MC) allocated to business and personal loans are difficult to compute (European Commission, 2007a), and accessing the availability of banking industry MC is equally hard to ascertain (European Commission, 2007b). Recent efforts by the European Microfinance Network (EMN) report that between 2012 and 2017 business loans were losing ground to personal loans both in the number (60% to 41%) and the value of disbursed loans (80% to 52%) as well as in terms of active borrowers (61% to 41%) (Bendig et al. 2014; Botti et al. 2016; Diriker et al. 2018). Personal loans are thus quickly catching up with business microloans and verged on €1 billion in 2017. Based on data about Eastern European countries sourced from the online peer-to-peer (P2P) crowdfunding platform Kiva, this paper examines the relation between soft information and prosocial P2P crowdfunding performance, in particular the funding speed, both for personal and for business loans. To the best of our knowledge, this paper represents the first to identify a relationship between soft information, measured by the text length describing the loan purpose on personal and business loans, and P2P crowdfunding performance. In keeping with previous studies (e.g., Dorfleitner et al., 2019a; Dorfleitner and Oswald, 2016), we apply a censored tobit regression model to predict the speed of loan funding on Kiva, by controlling for field partner, loan, borrower, and socioeconomic-geopolitical characteristics respectively. We furthermore deployed two datasets: the Kiva P2P crowdfunding platform and the World Bank. The Kiva’s dataset comprises 29,739 loans applied for between 2011 to 2018 from five European countries (two countries from the lower middle-income group: the Republic of Moldova and Ukraine, and three from the upper middle-income group: Albania, Armenia, and Georgia). This paper identifies how applying for personal loans increases the speed of funding time compared to business loans. Additionally, the results support the hypothesis of a quasi-U-shaped relationship between soft information and funding speed but applicable only to business loans. We provide new evidence on the relationship between personal versus business loans and crowdfunding performance. The resulting policy recommendations suggest P2P crowdfunding may require a greater focus on personal loans which constitute the “weakest link” in P2P lending marketplaces such as Kiva and furthermore gain less support from lenders. The results provide insights about microentrepreneurs to lenders with investing in education, skills and entrepreneurial training therefore appearing as crucial to their business success in line with thematic objective 10 (FI-Compass, 2018, 2016)